How effective and how expensive are interventions to reduce sedentary behavior? An umbrella review and meta‐analysis. (23rd January 2022) - Lam, Kevin; Baurecht, Hansjörg; Pahmeier, Kathrin; Niemann, Anja; Romberg, Carolin; Biermann‐Stallwitz, Janine; Neusser, Silke; Wasem, Jürgen; Mugler, Nida; Welker, Christine; Leitzmann, Michael; Jochem, Carmen
Summary: A reduction in sedentary behavior (SB) can contribute to the prevention of chronic diseases. This is the first umbrella review that summarizes the effectiveness and monetary costs of different types of interventions to reduce SB across all age groups and populations in different settings. We comprehensively searched seven databases for systematic reviews and meta‐analyses and conducted an umbrella review of the effects of interventions to reduce SB. Additionally, we performed a meta‐analysis of primary studies included in the umbrella review. Furthermore, we analyzed health economic aspects of interventions to reduce SB. We included 40 systematic reviews in our umbrella review, with 136 primary studies suitable for further meta‐analyses. We found that interventions targeting the physical environment reduce SB most effectively in the majority of populations and settings. Workplace interventions reduced SB by −89.83 min/day (95% CI −124.58 to −55.09; p ≤ 0.0001). Twenty‐two of 169 primary studies (13.0%) contained health economic information. The intervention costs per participant ranged from €0 to €3587. Our findings demonstrate that physical environment interventions most effectively reduce SB in a majority of populations and settings. Health economic information was reported in few studies and was mostly restricted to acquisition costs. Abstract :